Breaking the Barrier of Cancer through Papaya Extract and their Formulation - Saha, Sumana; Giri, Tapan K. (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: In the last decade, many new avenues of cancer treatment have opened up but the costs of treatment have sky-rocketed too. Hence, screening of indigenously available plant and animal resources for anti-carcinogenic potential is an important branch of anticancer research. The effort has been made through this comprehensive review to highlight the recent developments of anticancer therapies using different parts of papaya plant extract. Methods: In search of the naturally existing animals and plants for anticarcinogenic potential, papaya plant has been exploited by the scientist working in this research field. A widespread literature search was performed for writing this review. Results: Different constituents of Carica papaya responsible for anticancer activities have been discussed. Papaya extract for the treatment of breast, liver, blood, pancreas, skin, prostate, and colon cancer have also been reported. Finally, the various formulation approach using Carica papaya extract have been highlighted. Conclusion: The information provided in this review might be useful for researchers in designing of novel formulation of Carica papaya extract for the treatment of cancer.
Keywords: apoptosis